Sejarah pelaksanaan hak pewarisan pusaka di zaman Jahiliyyah dan zaman pasca Islam: Kajian perbandingan - Ahmad, Faridah; Mohd Nor, Fauziah; Azhar, Alias (Universiti Utara Malaysia Press, 2017)
This article discusses about the difference between the inheritance rights of heirs during the period of Jahiliah and after Islam.The study aims to comprehensively understand and to systematically and objectively strengthen the development of information about the historical perspective of the implementation of inheritance rights of heirs during the period of Jahiliah (before Islam) and post-Islamic era. The study employs qualitative method by exploring the old-time phenomena that happened during the period of Jahiliah and after Islam in the implementation of inheritance rights. The research outcome shows that implementation of inheritance rights during the post-Islamic era brings more justice than during the period of Jahiliah which are more discriminative in nature especially from the espect of marriage relationship. The situations happened during these two eras indicate the wide gap between them where the determination of inheritance rights during the post-Islamic era is more just and complete where as during the period of Jahiliah such determination was based on limited human thinking and desire which has led to injustise especially towards women and children.